(untitled) (Lundiana: International Journal of Biodiversity, 2009)
We describe the downy chick of Aramides saracura (Spix, 1825) based on individuals captured in the states of Rio Grande do Sul (3) and Minas Gerais (2), Brazil. The downy plumage is predominantly black, with the top of the head brownish. The egg tooth was present in two specimens. The downy chick of A. saracura differs from those of Aramides cajanea (Statius Müller, 1776) especially by the absence of rusty and brownish tones in their underparts.